Intikhab-e-Kalam : Majaz - Majaz; Edited and introduced by Raza Kazmi, Muhammad (Karachi Oxford University Press, 2011)
This book contains selected poems of Majaz who was the poet most representative of his age, struggling for independence as well as seeking social emancipation. He was an asset to the Progressive Writers Movement as attested by all his contemporaries and comrades. Even today, 50 years after his mysterious death, Majaz exercises a spell over every succeeding generation of poets and critics.
Keywords: Urdu Literature - Poetry -- Poetry in Urdu -- Urdu Literature - Poetry -- Intikhab e Kalam : Majaz